ALUR KLAIM ASURANSI KESEHATAN TERHADAP PIHAK KE-3 DI RUMAH SAKIT HERMINA ARCAMANIK BANDUNG - Dilla Oktavitia Sjachrizal; Hana Viranty Kahdini; Irda Sari (Media Bina Ilmiah, 2022)
Health care facilities are responsible for protecting health information contained in medical records against possible loss, damage, falsification, and unauthorized access. Maintain the confidentiality of information, accuracy of information, and ease of access to information which are the demands of health service organizations and health practitioners as well as authorized third parties. Overall security (security), privacy (privacy), confidentiality (confidentiality) and safety (safety) is a device that fortifies information in medical records. The sample of this research is the director of the hospital, the head of the medical record and the medical record officer. Analysis of the data used is the result of field work practices and the results of interviews conducted. The purpose of this research is to identify users of medical record information, especially 3rd party insurance claims. Conclusion There needs to be a review of procedures regarding the release of information for 3rd parties in documenting Hermina Arcamanik hospital.